PATOLOGI BIROKRASI DI BADAN KEPEGAWAIAN DAERAH KABUPATEN SEMARANG - Dwi Nur Purwandri; Rina Martini (Journal of Politic and Government Studies, 2013)
In Semarang District Regional Employment Board to be a very important government agency. This is because one of the tasks is organizing pokonya monitoring, evaluation, and reporting on the implementation of the tasks field of personnel, training and education that includes planning and employee development, education and training, and mutation. With this task BKD to "police" for civil servants throughout the Semarang District. But in reality it is still a lot of BKD employees who violate the adult is called a bureaucratic pathology. This study used quantitative research type descriptive analytic approach. Data collection techniques used in this study kuesiner, interviews and observation / direct observation in the field.The results of this study indicate that the presence of pathology birorasi in Semarang District Personnel Board. Besides many other types of bureaucratic pathologies that exist in Semarang District Personnel Board. Efforts to mitigate them is still not maximized, both the efforts of the local government itself or from the central government.In this study described the types of pathologies that occur in Semarang District Personnel Board. Most types of pathology that occurs due to the bureaucracy itself. Bureaucratic culture since antiquity still can not be changed by the bureaucracy itself. In doing errands a day much of the bureaucracy that is not maximized in the run, especially the bureaucracy associated with the service. Parigma changes still needed in the bureaucracy itself.Efforts to reduce bureaucratic pathologies are still few and not comprehensive in local government agencies. Efforts are made still seem half-and lack of seriousness of the government, both national and local governments to reduce bureaucracy pathology. However, the Semarang District BKD fewer still that effort, with coordination between members is carried out every week. However, it is still far from perfect to reduce bureaucratic pathologies that occur.Keywords: Birkrasi, Pathology Bureaucracy, Bureaucracy Effort Reduces Pathology, Pathology Constraints to Reduce Bureaucracy